The Emerging International Knowledge Exchange Barrier in Virtual Teacher Communities - Pirkkalainen, Henri; Jokinen, Jussi; Pawlowski, Jan (Proceedings of the 20th International Academic Mindtrek Conference, 2016)
Openness in education has sought its way to practice in schools as in universities. Many strategies and concepts have emerged: from openly shared resources to open practices to improve the access to and the quality of education. The knowledge exchange of educators has been seen a crucial activity in reaching and sustaining openness. This article analyses a typical knowledge exchange activity in schools: European teachers were engaged in virtual OER communities to exchange teaching resources as well as experiences about using OER and ICT in education. We applied technology acceptance framework and studied a potential barrier of international knowledge exchange. The findings of the study show surprising results: the willingness to exchange teaching materials within global virtual teacher communities decreases as schools mature in using OER and ICT. This study serves especially as a discussion opener for sustaining discourse and peer support in teacher virtual communities that strive for openness and international knowledge exchange. The findings have strong practical implications for the open education domain as well as for school / teacher development in general.
KerkoCite.ItemAlsoKnownAs: 10.1145/2994310.2994318 10/gf62h8 2129771:8JCM6QAV
Keywords: knowledge exchange; open education; teacher networks; technology acceptance; virtual community